Myosin-dependent cell-cell communication controls synchronicity of division in acute and chronic stages of Toxoplasma gondii - Karine Frénal (Nature Portfolio, 2017)
The mechanism by whichToxoplasma gondiiachieves synchronized cell division is incompletely understood. Here, the authors identify an intravacuolar cell-cell communication that ensures synchronized division and depends on myosin I.